PENGARUH TERAPI AKUPRESUR DENGAN JARI TANGAN TERHADAP PENURUNAN KECEMASAN DAN KELUHAN PADA WANITA MENOPAUSE - Purnama Dewi, Bela; H.Soebyakto, Diana; Fitriana, Eka (Jurnal Kesehatan dan Pembangunan, 2025)
Menopause is a natural biological process that occurs in every woman, marked by the cessation of the menstrual cycle due to declining estrogen levels. This phase is often accompanied by various physical and psychological complaints, such as anxiety, sleep disturbances, and muscle pain. One non-drug method that can be used to relieve these complaints is self-directed finger acupressure therapy. This study aims to determine the effect of finger acupressure therapy on reducing menopausal complaints and anxiety levels in menopausal women. The study design used a pre-experimental approach with a one-group pretest-posttest approach. A total of 60 menopausal women who met the inclusion criteria were selected through a purposive sampling technique. The intervention was carried out for 6 days, each session lasting 15–20 minutes. Data were collected using the HARS questionnaire to measure anxiety and the MRS to assess menopausal symptoms. Data analysis using the Wilcoxon test showed a significant reduction in anxiety levels (Z = -6.861; p = 0.001) and menopausal complaints (Z = -7.681; p = 0.001) after acupressure therapy. The majority of participants experienced a reduction in anxiety levels from moderate to mild, and physical complaints decreased from moderate to mild or nonexistent. Self-acupressure therapy using the fingers has been shown to be effective in reducing anxiety and menopausal complaints and can be a safe, practical, and self-administered non-pharmacological therapy option at home.